Research status and recent advances of lupus podocytopathy - Yang Meng; Wei Wei; Liu Rui-chan; Wang Ming-ao; Sui Man-shu (Linchuang shenzangbing zazhi)
As a special type of lupus nephritis, lupus podocytopathy（LP）is characterized by diffuse epithelial cell foot process effacement and absence of peripheral capillary wall proliferation and immune complex deposition.Currently the pathogenesis of LP has remained elusive.Using glucocorticoids and immunosuppressive agents can alleviate the severity of disease.However, high recurrence rate of LP has become a thorny problem.This review summarized the histopathology, pathogenesis and treatment of LP.